A general approach to access 5, 6-dihydroindolo-naphthyridine ring system. Issue 14 (5th April 2017) - He, Shuwen; Li, Peng; Dai, Xing; Liu, Hong; Lai, Zhong; Xiao, Dong; McComas, Casey C.; Du, Chunyan; Liu, Yuehui; Yin, Jingjun; Dang, Qun; Zorn, Nicolas; et al.
Graphical abstract: Highlights: A novel intramolecular cyclization gives access to the title ring system. Various precursors containing a six-membered azine are tolerated. This method affords 2c with a sterically congested C next to indole N. Abstract: We report a general approach for the synthesis of 5, 6-dihydroindolo-naphthyridine ring system via an intramolecular cyclization of the indole NH to an alkene moiety as the key step.